Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1, 15-(2x-3)=6
<=>2x-3=15-6
<=>2x=15-6+3
<=>2x=12
<=>x=12:2
<=>x=6
Vậy x=6
2, (x-2).3=3\(^2\)
<=>x-2=3\(^2\):3
<=>x-2=9:3
<=>x=9:3-2
<=>x=1
vậy x=1
3, (x+7)-25=13
<=>x+7=13+25
<=>x=13+25-7
<=>x=31
Vậy x=31
4, 450:(x-190)=50
<=>x-190=450:50
<=>x=450:50+/ 190
<=>x=199
Vậy x=199
5, 3 \(^x\)x 2=18
<=>3\(^x\)=18:2
<=>3\(^x\)=9=3\(^2\)
=>x=2
vậy x=2
a.(17.x-25):8+65=9^2
(17.x-25):8+65=81
(17.x-25):8=81-65
(17.x-25):8=16
17.x-25=16.8
17.x-25=128
17.x=128+25
17.x=153
x=153:17=9
b.720:[41-(2x-5)]=2^3.5
720:[41-(2x-5)]=40
41-(2x-5)=720:40
41-(2x-5)=18
2x-5=41-18
2x-5=23
2x=23+5
2x=28
x=28:2=14
c.(50-6x).18=2^3.3^2.5
(50-6x).18=360
50-6x=360:18
50-6x=20
6x=50-20
6x=30
x=30:6=5
d.2x-2^3.3^2=138
2x-72=138
2x=138+72
2x=210
x=210:2=105
a, \(\frac{x}{12}=-\frac{1}{24}-\frac{1}{8}\Leftrightarrow\frac{x}{12}=-\frac{1}{6}\Leftrightarrow6x=-12\Leftrightarrow x=-2\)
b, \(\frac{2}{3}x=\frac{1}{2}x+\frac{15}{12}\Leftrightarrow\frac{2x}{3}=\frac{x}{2}+\frac{15}{12}\Leftrightarrow\frac{4x}{6}-\frac{3x}{6}=\frac{15}{12}\Leftrightarrow\frac{x}{6}=\frac{15}{12}\Leftrightarrow x=\frac{15}{2}\)
c, \(\left|\frac{3}{4}-2x\right|+\frac{1}{6}=\frac{9}{2}\Leftrightarrow\left|\frac{3}{4}-2x\right|=\frac{13}{3}\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{3}{4}-2x=\frac{13}{3}\\\frac{3}{4}-2x=-\frac{13}{3}\end{cases}\Leftrightarrow\orbr{\begin{cases}2x=-\frac{43}{12}\\2x=\frac{61}{12}\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-\frac{43}{24}\\x=\frac{61}{24}\end{cases}}}\)
1/ 1 + (-2) + 3 + (-4) + . . . + 19 + (-20)
=1-2+3-4+...+19-20
=(1-2)+(3-4)+...+(19-20)
=(-1)+(-1)+...+(-1)
=(-1).10
=-10
2/ 1 – 2 + 3 – 4 + . . . + 99 – 100
=(1-2)+(3-4)+...+(99-100)
=(-1)+(-1)+...+(-1)
=(-1).50
=-50
3/ 2 – 4 + 6 – 8 + . . . + 48 – 50
=(2-4)+(6-8)+...+(48-50)
=(-2)+(-2)+...+(-2)
=(-2).13
=-26
4/ – 1 + 3 – 5 + 7 - . . . . + 97 – 99
=(-1)+(3-5)+(7-9)+...+(97-99)
=(-1)+(-2)+(-2)+...+(-2)
=(-1)+(-2).45
=(-1)+(-90)
=(-91)
5/ 1 + 2 – 3 – 4 + . . . . + 97 + 98 – 99 - 100
=(1+2-3-4)+...+(97 + 98 – 99 - 100)
=(-4)+...+(-4)
=(-4).25
=-100
\(HT\)
1/ \(1+(-2)+3+(-4)+...+19+(-20)\)
\(=(-1+3+5+...+19)-(2+4+6+...+20)\)
\(=(19-1):2+1=10\)
\(=(1+19).10:2-(20+2).10:2\)
\(=100-110\)
\(=-10\)
2/ \(1 – 2 + 3 – 4 + . . . + 99 – 100\)
\(= ( 1 - 2 ) + ( 3 - 4) + .... + ( 99 - 100 )\)
\(= -1 + ( -1) + ....+ ( -1)\)
\(=(-1).50\)
\(=-50\)
3/ \( 2 – 4 + 6 – 8 + . . . + 48 – 50\)
\(= 2 +( – 4 + 6)+( – 8+10) + . . . +( -44+46)+ ( 48 – 50)\)
\(= 2+2+2+...+2+( -2) \)
\(= 2.12 +( -2 ) \)
\(=22\)
4/ \(-1+3-5+7-...+97-99\)
\(= ( -1 + 3 ) + ( -5 + 7 )+....+( -93 +95 ) + ( 97 - 99 )\)
\(= -2+( -2)+...+( -2)+2\)
\(= -2.24+2\)
\(=-46\)
5/ \( 1+2-3-4+...+97+98-99-100\)
\(= ( 1+2-3-4)+...+( 97+98-99-100)\)
\(= -4+...+( -4)\)
\(=(-4).25\)
\(=-100\)
a) 2x - 3 = x + 1/2
<=> 2x - 3 = 1/2x + 1/2
<=> 2x - 3 - 1/2x = 1/2
<=> 3/2x - 3 = 1/2
<=> 3/2x = 1/2 + 3
<=> 3/2x = 7/2
<=> x = 7/2 : 3/2
<=> x = 7/3
=> x = 7/3
\(a,2x-3=x+\frac{1}{2}\)
\(2x-3=\frac{1}{2}x+\frac{1}{2}\)
\(2x-3-\frac{1}{2}x=\frac{1}{2}\)
\(\frac{3}{2}x-3=\frac{1}{2}\)
\(\frac{3}{2}x=\frac{1}{2}+3\)
\(\frac{3}{2}x=\frac{7}{2}\)
\(x=\frac{7}{2}:\frac{3}{2}\)
\(x=\frac{14}{6}=\frac{7}{3}\)
\(\)B làm tương tự
\(2.\left(2x-1\right)^2=50\\ \Rightarrow\left(2x-1\right)^2=50:2\\ \Rightarrow\left(2x-1\right)^2=25\\ \Rightarrow\left(2x-1\right)^2=\left(\pm5\right)^2\\ \Rightarrow\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)